Exploring the Attributes and Perceptions of Photography in Action Spaces on International Scales - Barbora Kováčová; Dadíková Natália (Interdisciplinary Science Studies, 2025)
The article examines the intersection of action photography and the concept of embodied experience, particularly in the context of ageing individuals (Smith, 2020). Action photography is explored as a dynamic medium that transcends mere documentation, serving as an expressive artistic form capable of capturing narratives and emotions in fleeting moments. It emphasizes the technical demands of action photography, such as mastering shutter speed, aperture, and focal length, to depict the vibrancy and energy of fast-paced environments (Doe, 2021). Alongside this exploration of visual art, the article delves into the significance of art action as a powerful tool for combating stagnation in physical, emotional, and social spheres among older adults. As they confront feelings of isolation and disconnection, engaging in creative expressions—such as movement-based art forms, painting, and gardening—enables seniors to reconnect with their bodies, tap into their creativity, and foster social connections. By reflecting on life experiences through art, older adults can reawaken a sense of vitality and purpose. The article highlights the international dimensions of photography as a tool for cultural diplomacy. By showcasing shared human experiences and cultural expressions, photography serves as a universal language that transcends borders, promoting dialogue and empathy among different cultures. The dual focus of this article illustrates how both action photography and embodied experience through art can transform individual narratives, promote meaningful engagement, and enrich the human experience across the lifespan.